Ultrasound-Assisted Extraction of Anthocyanins from Red Rose Petals and New Spectrophotometric Methods for the Determination of Total Monomeric Anthocyanins - Ozgur, Mahmure Ustun; Cimen, Emrah (AOAC INT, 2018)
In this study, four extraction technologies for the extraction of anthocyanins (Acyns) from red rose petals (RRPs) were investigated and compared, including ultrasound-assisted extraction (UAE), reflux extraction, Soxhiet extraction, and marinated extraction. UAE was the most suitable for the extraction of Acyns from RRPs because of its high extraction efficiency and short extraction time. The results showed that the best conditions for UAE are an extraction solution of ethanol-0.1 N HCl (80 + 20, v/v), a solid-to-liquid ratio of 1:40 g/mL, a temperature of 30 degrees C, and an extraction time of 15 min performed three times. Using such conditions, 320.4 mg Acyns/100 g RRPs was extracted. UAE was followed by two new difference spectrophotometric (DS) methods, which were developed for the fast and simple determination of Acyns in RRPs. Under the optimum experimental conditions, a linear response was observed for Acyns in the range of 12.5-62.5 mu g/mL for the two proposed methods, with correlation coefficients (r) ranging from 0.9988 to 0.9995. The mean recovery values of Acyns for the DS methods were in the range of 99.8-101.5%, and the RSD was 0.5%. The respective LOD and the LOQ values were 1.4 and 4.8 for DS1 and 1.1 and 3.6 mu g/mL for DS2. The stability of Acyns was also studied.
Keywords: PERFORMANCE LIQUID-CHROMATOGRAPHY; MASS-SPECTROMETRY; L.; RASPBERRIES; COLORANTS; JUICES; FRUITS; Chemistry; Food Science & Technology